2011
DOI: 10.1111/j.1365-2044.2011.06649.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised control trial to determine if use of the iResus©application on a smart phone improves the performance of an advanced life support provider in a simulated medical emergency*

Abstract: SummaryThis study sought to determine whether using the Resuscitation Council UK's iResus Ó application on a smart phone improves the performance of doctors trained in advanced life support in a simulated emergency. Thirty-one doctors (advanced life support-trained within the previous 48 months) were recruited. All received identical training using the smart phone and the iResus application. The participants were randomly assigned to a control group (no smart phone) and a test group (access to iResus on smart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
100
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 23 publications
4
100
0
Order By: Relevance
“…Given the evidence of smartphones assisting clinical practice 11,13 and the prevalence of use in our study population, it was surprising to find that only 16% had a mobile phone provided by their clinical/healthcare workplace and of note, none were smartphones. Consequently, most healthcare professionals used their privately owned mobile within clinical practice identifying that this was because their clinical/healthcare workplace did not provide them with one (irrespective of type -i.e., smartphone or non-smartphone).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Given the evidence of smartphones assisting clinical practice 11,13 and the prevalence of use in our study population, it was surprising to find that only 16% had a mobile phone provided by their clinical/healthcare workplace and of note, none were smartphones. Consequently, most healthcare professionals used their privately owned mobile within clinical practice identifying that this was because their clinical/healthcare workplace did not provide them with one (irrespective of type -i.e., smartphone or non-smartphone).…”
Section: Discussionmentioning
confidence: 88%
“…Thus a few studies have evaluated the efficacy of some apps [11][12][13][14][15] . For example, Flannigan and McAloon found that drug dosage calculator apps increases doctors' and medical students' accuracy and confidence in regards to drug dosage calculations 11 , whereas Low et al found that a specifically designed app improves healthcare professionals' performance in a simulated cardiac arrest emergency scenario 13 . On the contrary, Zanner et al found that nonmedically trained individuals' performance of cardiopulmonary resuscitation in a hypothetical emergency scenario was slower in those using a specifically designed app compared to those without the app 14 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In anaesthetic practice they have been reported for monitoring neuromuscular function [4], measuring 15-degree tilt in obstetric patients [5] and as an aid during resuscitation [6]. The rise in the use of mobile phones, from concern over their use near sensitive medical devices [7] to their ubiquitous presence in all clinical areas [8], and now their use as medical devices themselves, is extraordinary.…”
mentioning
confidence: 99%